Rediscovery of the enigmatic blind snake genus Xenotyphlops in northern Madagascar, with description of a new species (Serpentes: Typhlopidae) - Wallach, Van; Mercurio, Vincenzo; Andreone, Franco (Zootaxa, 2007)
After more than a century the rare blind snake genus Xenotyphlops Wallach & Ineich (1996) has been rediscovered in Madagascar, with the collection of a specimen from the arid northern part of the country. This represents only the third known Xenotyphlops specimen and establishes the first precise locality for the genus. As it differs from Xenotyphlops grandidieri (Mocquard) in several external and numerous internal features, it is here described as a new species.